Ruan Yuan, 1764-1849 : the life and work of a major scholar-official in nineteenth-century China before the Opium War - Wei, Betty Peh-Tʻi, 1930- (Hong Kong University Press ; Eurospan [distributor], 2006)
"This book explores the life and work of Ruan Yuan (1764-1849), a scholar-official of renown in mid-Qing China prior to the Opium War, before traditional institutions and values became altered by incursions from the West. His distinction as an official, scholar, and patron of learning has been recognized by both his contemporaries and modern scholars. He was also exulted as an honest official and an exemplary man of the 'Confucian persuasion'. His name is mentioned in almost all the works on Qing history or Chinese classics because of the wide range of his research and publications. A number of these publications are still being reprinted today." "This is the first full-length biography of Ruan Yuan in English, and the only one focusing on all aspects of the man's life and work in the context of his time. It follows Ruan Yuan from his childhood in Yangzhou, expansion of his intellectual horizons and political network in Beijing, his long service in the provinces handling some of the most thorny issues of the day in security and control, to the glory as a senior statesman in the capital, and retirement in Yangzhou."--Jacket.